2022
DOI: 10.1590/0001-3765202220200733
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data reveal multiple lineages of Scinax nebulosus (Spix, 1824) (Anura: Hylidae) with Plio-Pleistocene diversification in different Brazilian regions

Abstract: To understand the organism's history, we can start assessing the complexity of the biome where they occur. In this study, we used a region of the mitochondrial genome, the rRNA 16S, to evaluate the genetic differentiation in Scinax nebulosus along with its geographical range highlighting important Brazilian biomes as Restinga, Cerrado, Amazon, and Atlantic Forest. Geographically structured genetic divergence was observed within the species S. nebulosus. The values of the fi xation index (Ф st ) and the pairwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…3 and 5 (results not shown). Freitas et al (2022) reported a number of lineages under the name S. nebulosus ; it is unclear if one of them (they included samples from Goiás) corresponds to S. constrictus . Since the authors did not inform GenBank accession numbers, we do not have direct evidence to compare the lineages of their paper with those inferred in the present study.…”
mentioning
confidence: 99%
“…3 and 5 (results not shown). Freitas et al (2022) reported a number of lineages under the name S. nebulosus ; it is unclear if one of them (they included samples from Goiás) corresponds to S. constrictus . Since the authors did not inform GenBank accession numbers, we do not have direct evidence to compare the lineages of their paper with those inferred in the present study.…”
mentioning
confidence: 99%